Pengaruh Kecerdasan Emosional, Penghargaan Dan Kepemimpinan Transformasional Terhadap Kepuasan Kerja Pada Pt Catur Mitra Sejati Sentosa (Mitra 10) - Vania Lystia Putri; Hannes Widjaja (Jurnal Manajerial Dan Kewirausahaan, 2019)
The purpose of this study is to to find out the effect of emotional intelligence, reward and transformational leadership on job satisfaction on PT Catur Mitra Sejati Sentosa (Mitra 10). The hypotheses are tested towards 78 employees from PT Catur Mitra Sejati Sentosa (Mitra 10) head office which was selected by using purposive sampling technique based on the status of respondents who specified. Data analysis technique using Structural Equation Modelling Partial Least Square (SEM PLS) method. The result of this study shows that emotional intelligence, reward and transformational leadership have a positive and significant effect on job satisfaction.